A protocol for literature triage in online learning for the net-generation nursing and allied health care students - Maryam Ateya; Ebrahim Khalil; Sara Rasheed; Govindaraj Vaithinathan Asokan (MDPI AG, 2015)
Nursing and allied health care students use online learning resources with their own perspective of learning, often combined with curiosity. Although, students are overwhelmed with access to an enormous pool of information, we hypothesized that students may not possess the skills to appraise the merits of all online resources. Our pilot survey results have shown that students' knowledge of literature appraisal is inadequate. Circumventing this barrier requires adopting a three-phase protocol for literature triage such as: selection, appraisal, and critical reading. These skills would facilitate assessing all aspects of the literature, and identifying the best learning material.